Protective role of Punica granatum juice in inhibit nephrotoxicity Induced by amikacin in albino Rabbits - Hazim I. Ahmad; Sabe Kh. Al-Tai (Tikrit Journal of Pure Science)
The current investigation aimed to evaluate the role of Punica granatum juice extract to reduce nephrotoxic formation by amikacin in male and female albino rabbits by measuring some criteria for biochemical functions, such as creatinine, urea, albumin, total protein. Given amikacin (80mg/ kg) daily by injection in muscle for period  of 15 days caused  a significant increase at the level of (p ≤ 0.05)in the concentration of creatinine, and urea in the serum compared with the group control, while decreased the concentration of albumin and total protein significantly compared  with the control group. The rabbits given orally total dose of 100ml several time of amikacin daily pomegranate juice, a concentration of 40%, concomitantly with the injection in muscle at aldose of (80) mg/kg/day) has recorded a significant decrease in the concentrations of creatinine and urea compared with the group of rabbits treated with amikacin only, and  increased significantly the albumin and total protein compared with the control group treated with amikacin only.